2016
DOI: 10.1007/s10712-016-9365-3
|View full text |Cite
|
Sign up to set email alerts
|

The Global S $$_1$$ 1 Tide in Earth’s Nutation

Abstract: Diurnal S tidal oscillations in the coupled atmosphere–ocean system induce small perturbations of Earth’s prograde annual nutation, but matching geophysical model estimates of this Sun-synchronous rotation signal with the observed effect in geodetic Very Long Baseline Interferometry (VLBI) data has thus far been elusive. The present study assesses the problem from a geophysical model perspective, using four modern-day atmospheric assimilation systems and a consistently forced barotropic ocean model that dissip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…The S1 signal, considered anomalous for long, has been further explained. Schindelegger et al (2016Schindelegger et al ( , 2017 showed that the S1 LOD estimate (6 s) determined from VLBI is in agreement with atmosphere-ocean excitation estimates. 3.…”
Section: Selected Outcomesmentioning
confidence: 59%
“…The S1 signal, considered anomalous for long, has been further explained. Schindelegger et al (2016Schindelegger et al ( , 2017 showed that the S1 LOD estimate (6 s) determined from VLBI is in agreement with atmosphere-ocean excitation estimates. 3.…”
Section: Selected Outcomesmentioning
confidence: 59%
“…These meteorological forcings include diurnal variations in air pressure and also small‐scale contributions from land‐sea breezes (Ray & Egbert, ; Rosenfeld, ). Numerical modeling (e.g., Ray & Egbert, ; Schindelegger et al, ) shows that the radiational part of the S 1 ocean tide can have amplitudes of a few centimeters in some regions (Arabian Sea, eastern Indian Ocean, and Okhotsk Sea) and that it dominates the solar diurnal gravitational component by an approximate factor of 5 throughout the ocean. Pugh and Woodworth () also point to possible spurious manifestations of S 1 in tide gauge measurements, related, for example, to the daily heating and cooling of thermally sensitive instruments.…”
Section: Potential Mechanisms Causing Changesmentioning
confidence: 99%
“…Codes from Einšpigel and Martinec (; see also http://geo.mff.cuni.cz/~einspigel/debot.html, accessed 14 June 2017) were adopted as time domain solver of the nonlinear shallow water equations with forcing from individual partial tides. Following up on earlier experiments (Schindelegger et al, ), we have stripped down the model to its very core to prepare for inclusion of the full SAL machinery. Writing the undisturbed water depth as H , the tidal surface displacement with respect to the moving seafloor as ζ , and the corresponding velocity vector u as depth‐integrated volume transport U = u H , the one‐layer momentum and mass conservation equations read boldU∂t+f×boldU+·()boldUboldu=gH()ζζEQζSALFbFw+aH·σ ∂ζ∂t=·boldU where f is the Coriolis vector orientated along the local vertical, ∇ is the spherical del operator, ⊗ is the outer product, g denotes gravitational acceleration, ζ EQ refers to the equilibrium tide (Hendershott, ), and ζ SAL is the SAL elevation.…”
Section: Hydrodynamic Modelingmentioning
confidence: 99%